Interrogating green social prescribing in South Wales; A multi-stakeholder qualitative exploration. - Menna Brown; Katharine Sarah Aylett (PLoS ONE)
Background As an umbrella term, social prescribing offers varied routes into society which promise to support, enhance, and empower individual citizens to take control of their own health and wellbeing. Globally healthcare systems are struggling to cope with the increasing demands of an ageing population and the NHS (UK) is no exception. Social prescribing is heralded as a means to relieve the burden on primary care and provide support for the 20% of patients whose needs are non-medical. As such an increasing array of schemes are available, spanning five sub-sets: creative or nature-based referrals, welfare services, exercise referrals, education programmes or befriending support. Green social prescription offers significant potential to promote wellbeing and improve health outcomes. However limited research has explored this emergent sub-set. Aim Explore and interrogate the concept of social prescribing to understand how it is conceptualised, perceived, and experienced by different stakeholders involved in its coordination, delivery, and provision; At a time when it is being formalised in Wales, UK. Methods Using qualitative enquiry, from a social constructivist paradigm, stakeholder perspectives pertaining to current social prescribing models, pathways and actions in Wales were explored. Three multi-discipline research workshops and ten semi-structured, one-to-one interviews were conducted either in person or via zoom. Qualitative data were analysed thematically. Results 39 different stakeholders contributed. These included social prescribers, community connectors, service coordinators, third sector and voluntary organisation representatives, a general practitioner, occupational therapist, social enterprisers, academics and local area coordinators. Five themes were identified which revolved around stakeholders discussions of critical challenges pertaining to the delivery, provision, and evaluation of green social prescribing schemes in south Wales, UK. Tension between varying stakeholders was also evident, often preceded, or complicated by funding discrepancies, competition, and uncertainty. Stakeholders demanded clarity regarding evaluation outcomes and benchmarking across the sector. Conclusions To ensure the continued provision of social prescribing schemes which are highly valued by service users, voluntary and third sector organisations require funding security and stability. The delivery of green, nature-based, schemes require maintenance of trusting, long-term relationships with local service co-ordinators and referrers, secure equitable funding models and agreement over conceptual basis of social prescribing itself, particularly in relation to 'where' social prescribing is located within health and social care models. Without resolution and positive progress across these areas the continuation of local green schemes within local communities, which build resilience and support positive change for service users' health and wellbeing, is questionable.